Contextualization of Yusuf al-Qardhawi’s Concept of Moral Education: An Integrative Study with Character Education in Indonesia - Nazarmanto, Nazarmanto; Muchtar, Aflatun; Mukmin, Mukmin; Suryati, Suryati (Madania: Jurnal Kajian Keislaman, 2025)
This study aims to analyze the input, process, output, outcome, and contextualization of Yusuf al-Qardhawi’s concept of moral education within the framework of Indonesia’s character educatio. Data were collected from books, journals, articles, videos, and especially Yusuf al-Qardhawi’s works on moral education, using qualitative content analysis. The findings reveal that moral education consists of both software and hardware. The software includes a curriculum emphasizing morality toward Allah, the Prophet, oneself, other creatures, and the state, supported by both soft skills and hard skills activities. The hardware consists of teachers and students, with teachers expected to possess pedagogical, personal, social, and professional competencies, strengthened through prayer, dhikr, and advice. The process is carried out through structured lesson planning that integrates materials, syllabi, teaching modules, media, methods, and facilities into the lesson plan (RPP), while learning activities cover opening to closing stages with appropriate methods, assessments, and classroom management. The output and outcome of Yusuf al-Qardhawi’s moral education are students who have faith and piety to Allah, love the Prophet, show noble character toward others, and respect all creation. In its contextualization, this study highlights that Yusuf al-Qardhawi’s moral values, such as compassion, humility, sincerity, patience, justice, moderation (wasathiyah), and balance (tawazun), are strongly relevant to character education in Indonesia. These values align with key traits promoted nationally, including religiosity, honesty, discipline, creativity, tolerance, democracy, nationalism, patriotism, respect, peace, and environmental care. The study affirms that Yusuf al-Qardhawi’s ideas provide a valuable contribution to strengthening character education in Indonesia. Penelitian ini bertujuan untuk menganalisis input, proses, output, outcome, dan kontekstualisasi konsep pendidikan moral Yusuf al-Qaradawi dalam kerangka pendidikan karakter di Indonesia. Data dikumpulkan dari buku, jurnal, artikel, video, dan terutama karya-karya al-Qardhawi tentang pendidikan moral, dengan menggunakan analisis isi kualitatif. Temuan penelitian menunjukkan bahwa pendidikan moral terdiri atas perangkat lunak (software) dan perangkat keras (hardware). Perangkat lunak mencakup kurikulum yang menekankan moralitas terhadap Allah, Nabi, diri sendiri, makhluk lain, dan negara, yang didukung oleh kegiatan soft skills dan hard skills.Perangkat keras terdiri atas guru dan peserta didik, di mana guru diharapkan memiliki kompetensi pedagogis, personal, sosial, dan profesional, yang diperkuat melalui doa, dzikir, dan nasihat. Proses dilaksanakan melalui perencanaan pembelajaran yang terstruktur dengan mengintegrasikan materi, silabus, modul ajar, media, metode, dan sarana ke dalam RPP, sementara kegiatan pembelajaran mencakup tahap pembukaan hingga penutupan dengan metode, penilaian, dan manajemen kelas. Output dan outcome dari pendidikan moral Yusuf al-Qardhawi adalah peserta didik yang beriman dan bertakwa kepada Allah, mencintai Nabi, berakhlak mulia terhadap sesama, serta menghormati seluruh ciptaan. Dalam konteks kontekstualisasi, penelitian ini menegaskan bahwa nilai-nilai moral Yusuf al-Qardhawi, seperti kasih sayang, kerendahan hati, ketulusan, kesabaran, keadilan, moderasi (wasathiyah), dan keseimbangan (tawazun), sangat relevan dengan pendidikan karakter di Indonesia. Nilai-nilai tersebut selaras dengan karakter utama yang dikembangkan secara nasional, termasuk religiusitas, kejujuran, kedisiplinan, kreativitas, toleransi, demokrasi, nasionalisme, patriotisme, sikap hormat, cinta damai, dan kepedulian terhadap lingkungan. Penelitian ini menegaskan bahwa gagasan Yusuf al-Qaradawi memberikan kontribusi berharga dalam memperkuat pendidikan karakter di Indonesia.